Team Based Project Learning Model on The MBKM Course in The Department of Nonformal Education - Abdul, Rahmat; Zubaidi, Muhammad; Mirnawati, Mira; Mobo, Froilan Delute (Universitas Negeri Semarang, 2022)
The PISA ranking places Indonesia in 2019 at 74th, or the 6th bottom of the 79 countries surveyed. From this data alone, we can describe how low the cognitive abilities or intelligence of Indonesian students are. In the education curriculum, the government has designed special standards so that Indonesian students are increasingly trained in their cognitive abilities, and are increasingly able to solve problems well. Freedom to learn is an idea that gives freedom to educators and students in determining the learning system. The purpose of the declaration of independent learning is to create a meaningful education and emphasize aspects of skills and experiences in learning. The spirit brought by the concept of independent learning is the flexibility and freedom in designing and managing learning for educational actors, ranging from educational institutions, educators, to students. The main programs are: the ease of opening new study programs, changes to the accreditation system for higher lecturers, the convenience of state higher education institutions becoming state universities with legal entities, and the right to study for three semesters outside the study program. Students are given the freedom to take credits outside the study program, three semesters which are meant in the form of 1 semester of opportunity to take courses outside the study program and 2 semesters of participating in learning activities outside of higher education. Various forms of learning activities outside of tertiary institutions, including conducting internships/work practices in industry or other workplaces, implementing community service projects in villages, teaching in educational units, participating in student exchanges, conducting research, conducting entrepreneurial activities, conducting studies/ independent projects, and following humanitarian programs. All these activities must be carried out by students with guidance from the lecturer. The learning process at the Merdeka Campus is one of the most essential manifestations of student-centered learning. Learning in the Merdeka Campus provides challenges and opportunities for the development of innovation, creativity, capacity, personality, and student needs, as well as developing independence in seeking and finding knowledge through realities and field dynamics such as ability requirements, real problems, social interaction, collaboration, self-management, performance demands, targets and achievements. Through an independent learning program that is well designed and implemented, students' hard and soft skills will be formed strongly.